The incidence of musculoskeletal system occupational diseases among tuberculosis laboratory workers - Gül, Tuğba; Gül, Serdar Savaş (The European Research Journal, 2018)
Objectives. Health care workers are exposed to various kinds of professional risks like needle stick injuries, lower back and back problems, allergies, violence and stress. Health care workers in tuberculosis laboratory are exposed to both infection and musculoskeletal system occupational disease risks because of using Class II, Type B biological safety cabinets and laboratory vortex equipment. This study was carried out to determine incidence rates and causes of the musculoskeletal system occupational diseases among health care workers in tuberculosis laboratories of two State hospitals in Ankara. Methods. Study population was composed of 16 laboratory workers in tuberculosis laboratories of two State hospitals in Ankara. Data was collected using a questionnaire.Results. Thirteen (81.2%) laboratory workers were male and three (18.8%) were female. The mean age of the subjects was 40.1 ± 7.0 years and average duration of occupation of subjects was 208.3 ± 11.6 month. According to the data, of the 16 personnel, 10 (62.5%) had occupational disease. Incidence rates of occupational diseases were as follows; 62.5% shoulder pain, 25.0% wrist pain and 18.8% elbow pain. Duration of their occupation was significantly associated with elbow pain (p = 0.037). There was a significant relationship between hand and wrist pain and smoking (p = 0.042). Seventy-five per cent of laboratory workers did not think they had enough information on occupational diseases, and 68.8% of them wanted to have information about occupational diseases. Discussion. The most prevalent occupational diseases among the tuberculosis laboratory workers in our sample were shoulder, elbow and wrist pains. Duration of occupation and smoking were associated with the incidence of occupational diseases.